Qualitative urinary organic acid analysis: 10 years of quality assurance - Peters, Verena; Bonham, James R.; Hoffmann, Georg F.; Scott, Camilla; Langhans, Claus-Dieter (Journal of inherited metabolic disease, 2016)
Over the last 10 years, a total of 90 urine samples from patients with metabolic disorders and controls were circulated to different laboratories in Europe and overseas, starting with 67 laboratories in 2005 and reaching 101 in 2014. The participants were asked to analyse the samples in their usual way and to prepare a report as if to a non-specialist pediatrician. The performance for the detection of fumarase deficiency, glutaric aciduria type I, isovaleric aciduria, methylmalonic aciduria, mevalonic aciduria, phenylketonuria and propionic aciduria was excellent (98-100 %). Over the last few years, detection has clearly improved for tyrosinaemia type I (39 % in 2008 to over 80 % in 2011/2014), maple syrup urine disease (85 % in 2005 to 98 % in 2012), hawkinsinuria (62 % in 2010 to 88 % in 2014), aminoacylase I deficiency (43 % in 2009 to 73 % in 2012) and 3-methylcrotonyl-CoA carboxylase deficiency (60 % in 2005 to 93 % by 2011). Normal urines were mostly considered as normal (83-100 %), but laboratories often made additional diagnostic suggestions. When the findings were unambiguous, the reports were mostly clear. However, when they were less obvious, the content and quality of reports varied greatly. Repetition of organic acid measurements on a fresh sample was rarely suggested, while more complex or invasive diagnostic strategies, including further metabolic screening or biopsy were recommended. Surprisingly very few participants suggested referral from the general paediatrician to a specialist metabolic centre to confirm a diagnosis and, if applicable, to initiate treatment despite evidence suggesting that this improves the outcome for patients with inherited metabolic disorders. The reliability of qualitative organic acid analysis has improved over the last few years. However, several aspects of reporting to non-specialists may need discussion and clinicians need to be aware of the uncertainty inherent in all forms of laboratory diagnostic analysis.
Published online: 4 May 2016
Gesehen am 12.10.2020